USE OF NUCLEAR METHODS IN THE ORGANIZATION OF THE WELL SECTION (Archive of Conferences, 2021)
Nuclear methods of geophysical research of wells are one of the most effective methods for determining a number of parameters that are measurable using electrical logging methods (natural radioactivity, bulk density, hydrogen content, elemental composition, ash content of coals). In addition, nuclear methods can be used not only in an open (not cased) wellbore, but also in a closed well, when many electrical methods are fundamentally inapplicable.